Search for Majorana neutrinos in same-sign WW scattering events from pp collisions at √s =13 TeV - Aad, Georges; Baltes, Lisa Marie; Bartels, Falk; Castillo, Florencia Luciana; Czurylo, Marta; Rio, Fernando del; Dittmeier, Sebastian; Dunford, Monica; Franchino, Silvia; Junkermann, Thomas; Klassen, Martin; Mkrtchyan, Tigran; et al. (The European physical journal. C, Particles and fields, 2023)
A search for Majorana neutrinos in same-sign W W scattering events is presented. The analysis uses √s = 13 TeV proton–proton collision data with an integrated luminosity of 140 fb−1 recorded during 2015–2018 by the ATLAS detector at the Large Hadron Collider. The analysis targets final states including exactly two same-sign muons and at least two hadronic jets well separated in rapidity. The modelling of the main backgrounds, from Standard Model samesign W W scattering and W Z production, is constrained with data in dedicated signal-depleted control regions. The distribution of the transverse momentum of the second-hardest muon is used to search for signals originating from a heavy Majorana neutrino with a mass between 50 GeV and 20 TeV. No significant excess is observed over the background expectation. The results are interpreted in a benchmark scenario of the Phenomenological Type-I Seesaw model. In addition, the sensitivity to the Weinberg operator is investigated. Upper limits at the 95% confidence level are placed on the squared muon-neutrino–heavy-neutrino mass-mixing matrix element |VμN |2 as a function of the heavy Majorana neutrino’s mass m N , and on the effective μμ Majorana neutrino mass |mμμ|.